Legal Review of Disputes Between Indigenous Communities and the Government Regarding Territorial Boundaries (Case Study of Marampa Village, Rongkong District, North Luwu Regency) - Anggun Sari Sahid; Abdain Abdain; Anita Marwing (Rule of Law Studies Journal, 2026)
Background:Disputes between indigenous communities and the government over territorial boundaries are a common occurrence in various regions across Indonesia. These conflicts are generally triggered by differing perspectives on determining territorial boundaries, with indigenous communities using a historical and traditional approach, while the government uses a formal administrative and mapping approach. Aims:This study aims to legally analyze the dispute between indigenous peoples and the government regarding territorial boundaries in Marampa Village, Rongkong District, North Luwu Regency, and to identify the factors causing the conflict and efforts to resolve it. Methods:This research uses a qualitative approach with a descriptive design. The approach employed includes normative and historical juridical approaches. Data were obtained through observation, interviews, and documentation, involving indigenous communities and village government officials as research informants. The data were then analyzed using qualitative analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. Result:The research results indicate that disputes between indigenous communities and the government regarding territorial boundaries are caused by differences in boundary determination methods, village expansion, lack of communication between indigenous communities and the government, and the government's lack of attention to the recognition of customary territories. Efforts to resolve the conflict are carried out through deliberation between the two parties and participatory mapping of customary territories. Conclusion: Boundary disputes between indigenous communities and the government are influenced by differing approaches to defining territory and a lack of coordination between the two parties. Therefore, more participatory policies and clearer legal recognition of indigenous territories are needed to minimize similar conflicts in the future.